Impact of Routine Fractional Flow Reserve on Management Decision and 1-Year Clinical Outcome of Patients With Acute Coronary Syndromes: PRIME-FFR (Insights From the POST-IT [Portuguese Study on the Evaluation of FFR-Guided Treatment of Coronary Disease] and R3F [French FFR Registry] Integrated Multicenter Registries - Implementation of FFR [Fractional Flow Reserve] in Routine Practice). (June 2017) - Van Belle, Eric; Baptista, Sergio-Bravo; Raposo, Luís; Henderson, John; Rioufol, Gilles; Santos, Lino; Pouillot, Christophe; Ramos, Ruben; Cuisset, Thomas; Calé, Rita; Teiger, Emmanuel; Jorge, Elisabete; et al.
Abstract : Background—: Fractional flow reserve (FFR) is not firmly established as a guide to treatment in patients with acute coronary syndromes (ACS). Primary goals were to evaluate the impact of integrating FFR on management decisions and on clinical outcome of patients with ACS undergoing coronary angiography, as compared with patients with stable coronary artery disease. Methods and Results—: R3F (French FFR Registry) and POST-IT (Portuguese Study on the Evaluation of FFR-Guided Treatment of Coronary Disease), sharing a common design, were pooled as PRIME-FFR (Insights From the POST-IT and R3F Integrated Multicenter Registries - Implementation of FFR in Routine Practice). Investigators prospectively defined management strategy based on angiography before performing FFR. Final decision after FFR and 1-year clinical outcome were recorded. From 1983 patients, in whom FFR was prospectively used to guide treatment, 533 sustained ACS (excluding acute ST-segment–elevation myocardial infarction). In ACS, FFR was performed in 1.4 lesions per patient, mostly in left anterior descending (58%), with a mean percent stenosis of 58±12% and a mean FFR of 0.82±0.09. In patients with ACS, reclassification by FFR was high and similar to those with non-ACS (38% versus 39%; P =NS). The pattern of reclassification was different, however, with less patients with ACS reclassified from revascularization to medical treatment compared with those with non-ACS ( P =0.01). In ACS, 1-year outcome of patients reclassified based on FFR (FFR against angiography) was as good as that of nonreclassified patients (FFR concordant with angiography), with no difference in major cardiovascular event (8.0% versus 11.6%; P =0.20) or symptoms (92.3% versus 94.8% angina free; P =0.25). Moreover, FFR-based deferral to medical treatment was as safe in patients with ACS as in patients with non-ACS (major cardiovascular event, 8.0% versus 8.5%; P =0.83; revascularization, 3.8% versus 5.9%; P =0.24; and freedom from angina, 93.6% versus 90.2%; P =0.35). These findings were confirmed in ACS explored at the culprit lesion. In patients (6%) in whom the information derived from FFR was disregarded, a dire outcome was observed. Conclusions—: Routine integration of FFR into the decision-making process of ACS patients with obstructive coronary artery disease is associated with a high reclassification rate of treatment (38%). A management strategy guided by FFR, divergent from that suggested by angiography, including revascularization deferral, is safe in ACS. Abstract : Supplemental Digital Content is available in the text.